Histologic effect of a postnatal slow-release GnRH agonist on feline gonads - Carranza Martin, Ana Cristina (2015)
In postnatal domestic cats, GnRH agonists suppressed fecal concentrations of sexual steroids and delayed puberty. The aim of this study was to describe the gross and microscopic morphometric effects of a single administration of the GnRH agonist, deslorelin acetate, on the gonads of postnatally treated cats. Twenty-seven postnatal male (n=14) and female (n=13) kittens were randomly assigned to one of the following treatment groups within the first 24hours of birth: deslorelin acetate (1.6mg, subcutaneous; DA, n=16) or control that remained untreated (CO, n=11) and spayed or castrated immediately after the onset of puberty. After surgical removal, the gonads were gross and histologically assessed. Sertoli cells also were examined immunohistochemically. Comparisons between the treatments were carried out by the Student t test. Gross gonadal wet weight and volume as well as gonadosomatic index were significantly lower in the DA than those in the CO males; these same parameters were not different in females. Primordial (461.4+3.0 vs. 1074.3+117.5; P<0.01), primary (59.1+13.5 vs. 165.4+24.6; P<0.01), and secondary (17.5+2.6 vs. 31.17+8.1; P<0.05) follicles per mm2 were decreased in DA than in CO gonads. Epididymal sperm motility and morphology were normal in all but two DA cats that had too few sperm to be evaluated. Germinal epithelial height (μm; 39.68+0.92 vs. 72.7+1.2; P<0.01) and most of their cellular components as well as the Sertoli (cm3; 0.1+0.02 vs. 0.24+0.05; P<0.01) cells were diminished in the DA cats. Gonadotropin-releasing hormone agonist endocrine disruption during the neonatal critical reproductive time window may have a potential as a contraceptive agent in domestic felids.